The Views of Whiteness as The Standard Beauty in Morrison’s The Bluest Eye - Amalia Herwinda Agustini (Universitas Sebelas Maret, 2025)
The objective of this research is to study the way Pecola Breedlove, the main character in The Bluest Eye, views whiteness as the standard of beauty, Morrison's historical and social conditions, and also Morrison’s worldview of the work. In order to achieve the objective, I use Lucien Goldmann’s theory of genetic structuralism. As the methodology, it is a combination between comprehension and explanation. In comprehension part, mental structure of society in the novel is being discussed. While in explanation part, it is the comparation of the mental structure in the novel and society in real life. The findings gained from comprehending the novel is that the way Pecola Breedlove’s obsession of whiteness as the standard of beauty is indeed a result of being pressured by the mental structure of society in the novel regarding the beauty standard. On the other hand, Toni Morrison also encountered the same mental structure of society regarding whiteness as the beauty standard in real life during the writing of The Bluest Eye. Hence, Morrison’s worldview is spreading the idea that whiteness is not the standard of beauty.